2023
DOI: 10.3389/fonc.2023.950732
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile as a novel prognostic predictor for patients with acute myeloid leukemia

Abstract: PurposeThis study investigated the relationship between serum lipid levels and clinical outcomes in acute myeloid leukemia (AML) by establishing a predictive risk classification model.MethodA total of 214 AML patients who were pathologically diagnosed and treated with standard induction chemotherapy at Sun Yat-Sen University Cancer Center were included. The patients were randomly divided into the training (n = 107) and validation (n=107) cohorts. Univariate and multivariate Cox analyses were used to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Increased cholesterol demand is an established feature of AML cells 56 , and upregulation of cholesterol biosynthesis genes has shown prognostic value in AML [57][58][59] . While the precise mechanisms by which cholesterol confers a survival advantage remain unclear, inhibiting cholesterol biosynthesis has been shown to sensitize AML cells to radiation and chemotherapy 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…Increased cholesterol demand is an established feature of AML cells 56 , and upregulation of cholesterol biosynthesis genes has shown prognostic value in AML [57][58][59] . While the precise mechanisms by which cholesterol confers a survival advantage remain unclear, inhibiting cholesterol biosynthesis has been shown to sensitize AML cells to radiation and chemotherapy 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…Lipid profiling of plasma samples from AML patients revealed an incresed concentration of phosphatidyl-inositol and free fatty acids in the plasma of patients with an unfavorable prognosis (n=5) compared to patients with a favorable prognosis (n=5) ( 81 ). Another study analyzing the serum lipid levels in 214 AML patient samples found, among others, apolipoprotein B and high-density lipoprotein cholesterol to be prognostic factors for the clinical outcome ( 82 ). Furthermore, AML blasts can induce the phosphorylation of hormone-sensitive lipase in bone marrow adipocytes and activate lipolysis, leading to the release of fatty acids from adipocytes ( 83 ).…”
Section: Aml Metabolismmentioning
confidence: 99%
“…Elevated circulating triglyceride and lower HDL-cholesterol levels have been consistently observed in ALL and AML [ 158 162 ]. Accordingly, overall survival in AML patients has been shown to be independently associated with elevated triglyceride and reduced HDL levels before treatment initiation [ 163 ]. Of note, this pattern is consistent with the so-called diabetic dyslipidemia, which likely emerges as a result of insulin resistance and increased production of large buoyant VLDL1 particles by the liver [ 164 , 165 ].…”
Section: Biological Mechanisms Associating Obesity With Leukemiamentioning
confidence: 99%